AGGRESSIVE BEHAVIOUR AND EMOTIONAL MATURITY OF EARLY ADOLESCENTS - R S, Reena (International Journal of Research -GRANTHAALAYAH, 2018)
The study conducted on aggressive behaviour and emotional maturity of early adolescent students. Survey method was adopted for the present study. A sample of 400 high school students was selected using the random sampling technique. The tools used in the study were Aggressive Behaviour Scale prepared by Km.Roma Pal (1971) and the same tool was validated by Krishna Raj (2012) and Emotional Maturity scale was developed by Dr Yashwir Singh and Mahesh Bhargava (1990). The investigator validated the items of the emotional maturity scale to check the suitability of the items. Percentage Analysis, “t” test, ANOVA, Scheffe test were the statistical techniques used in the study. The major finding of the study revealed that there is no significant relationship exists between aggressive behaviour and emotional maturity of early adolescent students.